AKSI BERGIZI UNTUK CEGAH ANEMIA: PENGALAMAN PROMOTIF-PREVENTIF DI PUSKESMAS CIHERANG, CIANJUR - Gumilang, Lani; Rabbani, Salma Damayanti; Susanti, Ari Indra; Mandiri, Ariyati (Universitas Padjadjaran, 2025)
The Aksi Bergizi Program is a school-based promotive and preventive intervention conducted by Universitas Padjadjaran’s KKN-PPM students in collaboration with Puskesmas Ciherang to address the high prevalence of anemia among adolescent girls. The program was implemented from January to February 2025 in three junior high schools in Cianjur Regency, involving 290 female students. Activities included education on nutrition and anemia, distribution and monitoring of iron supplementation (TTD), and the establishment of 71 Youth Health Cadres and Youth Ambassadors as peer change agents. Evaluation through pre- and post-tests showed an increase in students’ knowledge scores by 34.2%, from an average of 56.0 to 75.0. The participatory and collaborative approach between university students, schools, and health centers effectively enhanced awareness and adherence to TTD consumption, while supporting the program’s sustainability within the school environment. Program Aksi Bergizi merupakan intervensi promotif dan preventif berbasis sekolah yang dilaksanakan oleh mahasiswa KKN-PPM Universitas Padjadjaran bekerja sama dengan Puskesmas Ciherang, sebagai upaya menanggulangi tingginya prevalensi anemia pada remaja putri. Kegiatan berlangsung selama Januari–Februari 2025 di tiga SMP di Kabupaten Cianjur dengan melibatkan 290 siswi. Intervensi mencakup edukasi mengenai gizi dan anemia, distribusi serta pemantauan konsumsi tablet tambah darah (TTD), dan pembentukan agen perubahan sebaya berupa 71 Kader Kesehatan Remaja dan Duta Remaja. Evaluasi pre- dan post-test menunjukkan peningkatan skor pemahaman siswa sebesar 34,2% (dari rata-rata 56,0 menjadi 75,0). Pendekatan partisipatif dan kolaboratif antara mahasiswa, sekolah, dan puskesmas terbukti memperkuat kesadaran dan kepatuhan siswi dalam mengonsumsi TTD serta mendukung keberlanjutan program di lingkungan sekolah.